Spatial characterisation of natural terroir units for viticulture in the Bottelaryberg-Simonsberg-Helderberg winegrowing area - Carey, Victoria Anne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 2001.